INOVASI PEMBELAJARAN SASTRA JAWA BERBASIS KOMPETENSI MELALUI MEDIA WAYANG KANCIL - Suroso, Suroso; Suwardi, Suwardi; Widayat, Afendy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
Based on the analysis  of the field situation  there are some complaints by the elementary   students  to their  parents  that the  local  content  subject  of Javanese  literature   is  hard  to  learn  and  is  not  interesting   that  it  becomes something   frightening   them.   That  is  why  it  is  necessary   to  immediately found  the  way  out  that  it  is  fun  for  them  to  learn  the  subject.  Therefore, using  the  recent   advancement    of  science   and  technology   a  competence based  Javanese  literature   learning  through  the media  of Wayang  Kancil  are introduced.  The training  is organized  to answer  the following  questions:  (1) What  are  the  manifestations    of  the  competence-based    literature   learning through   the   media    of   Wayang    Kancil?   and   (2)   To   what   extent   the competence-based    literature   learning  through  the  media  of  Wayang  Kancil succeed   to  encourage    the   students   in  learning   the  subject   of  Javanese Literature?The  target  population   are  the  elementary  school  teachers  in Kulom Progo  regency  of  Y ogyakarta.   Each  of the  existing  subdistricts   sends  two teachers   that   the  total   participants    are  40  individuals.   The   activity   are centered    in    Sanggar    Kegiatan     Belajar    (SKB)    Kulon    Progo    (Dinas Pendidikan   Hall).  It  is conducted   using  the  method  of speech,  discussion, exercise,  and Wayang  Kancil  simulation.All  of  the  40  participants   are  able  to  practice  the  learning  process using the Wayang  Kancil.  It may be initiated  using  story telling  and also by singing  a  song.  They  succeed:   (1)  to  chose  or  create  an  interesting   story appropriate  with the need of the elementary  school  students,  (2) to make  use of the language  and various  messages  on good conduct  that are to transfer  to the  students   in  the   learning   process   through   the  media  of  the   Wayang Kancil,  and  (3) to  master  the  strategy  in selecting  the contextual   stories  in Kulon   Progo.   Subsequently,    the  participants    are:   (1)  well-motivated     in practicing  and doing  their job  with the media of the Wayang Kancil,  (2) with the pleasure  willing  to share their knowledge  and skills with their  colleagues in their  respective  districts,   (3) all of them  listen  the tutorial,  attending  the183184perform~nce    of.the   Way~ng   Kanc~1 and  in the  same  time  appreciating     it, (4) to  pr~ctlce    telh.ng   Kanc~l   story    III tu:n  using  the  media  of  the  Wayang Kancil,  (5! to  smg  Kancil  song,  Kancil  poem  reading  appropriate   with  the psyc.hoiogical developmen.t  ~f the .elementary school students,  (6) to practice p~aYlllg~he Wayan~  Kancil  III a SImple manner  without  any instrument,   but dlrec~ly III t~e learning  process,  (7) to organize  the simulation  of the Wayang Kancil learning.Key words: KBK, wayang kancil, Javanese literature